Pendampingan Ketatausahaan Madrasah di Pondok Pesantren Darussalam Ampah Kalimantan Tengah - Musyarapah; Sardimi; Marni; Rahmad Wahyudi; Muhammad Iqbal Purnama Adi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This article is the result of service to the community of the Postgraduate Islamic Education Management Masters Study Program in Iaian Palangka Raya regarding providing material and assistance regarding school administration management at the Darussalam Ampah Islamic boarding school in Central Kalimantan. The problems faced by schools are related to the management of school administration, including the management of correspondence and school administration services for religious teachers and female students. The administrative assistance activities that will be carried out are collaborative between lecturers and students of the IAIN Palangka Raya Postgraduate Islamic Education Management Masters study program, which is very relevant and important. The aim of this activity is to provide assistance to school administration in the form of correspondence management and school administration services. This activity received a positive and enthusiastic response from the leadership of the Islamic boarding school, the head of administration and all the ustadz and religious teachers who taught there. Community Service for the MPI Master's Program obtained the results of the discussion, namely that there is still a lot that needs to be improved in the administrative management system of the Darussalam Ampah Islamic boarding school in terms of managing correspondence and TU services. Service activities like this can be carried out regularly either in the same location or in different locations targeting people who really need services in terms of administrative management. Moreover, IAIN Postgraduate IAIN Palangka Raya has a Masters Study Program in Islamic Education Management so that it can be useful and useful. for Islamic educational institutions in Central Kalimantan.